Sports preparticipation evaluation for healthy adults: a consensus-based german guideline - Joisten, Christine; Hirschmüller, Anja; Bauer, Pascal; Baum, Erika; Behrens, Meinolf; Berrisch-Rahmel, Susanne; Berrsche, Gregor; Carlsohn, Anja; Cassel, Michael; DeZeuuw, Justus; Dörr, Gesine; Dreher, Michael; et al. (Sports medicine, 2025)
The benefits of physical activity are undisputed. However, adverse events can occur in rare cases, particularly during high-intensity or prolonged exercise. During physical activity, at-risk patients can experience major cardiac events, whereas adverse events affecting the musculoskeletal system are more common but less severe. A sports preparticipation evaluation (PPE) for apparently healthy adults is designed to detect at-risk individuals and prevent potentially fatal events. This guideline for conducting PPEs was developed by consensus among 16 medical societies and sports associations and is based on previously published guidelines and consensus papers. Sports medicine physicians and potential participants were also surveyed to assess the recommendations’ content, feasibility, and implementation. On the basis of the 20 recommendations developed and agreed upon by the abovementioned entities, PPE comprises individuals’ personal, family, and sports histories, as well as a physical examination. The need for additional examinations (e.g., laboratory parameters, echocardiograms, or stress tests) is determined on the basis of the PPE findings. This approach’s feasibility in various regions, including resource-limited settings, and the extent to which it prevents adverse or potentially fatal events, should be examined in future research.
Veröffentlicht: 03. Juli 2025
Gesehen am 13.11.2025